PELAKSANAAN TANGGUNG JAWAB PENGEMBANG (DEVELOPER) DALAM PEMENUHAN SERTIFIKAT KEPEMILIKAN RUMAH KEPADA PEMBELI RUMAH BERDASARKAN PERJANJIAN PENGIKATAN JUAL BELI PERUMAHAN - Vina Septhiani Muthia; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The need for housing as a residence or residence, both in urban and rural areas continues to increase. Various ways can be done to get land rights, one of which is commonly done is by buying and selling. Buying and selling which is an agreement between two parties that sell and the other party that purchases where in the transaction makes an agreement that contains the rights and obligations of both of which are stated in the binding agreement of sale and purchase. The time factor in an agreement is very important because it is an achievement of the parties to carry out what has been agreed by the parties. Implementation of the fulfillment of the contents of the agreement by the parties is also very important so that the agreement is carried out and not defaulted. So that the parties can take responsibility according to their rights and obligations in the agreement until the sale and purchase is complete.The purpose of this study is to find out and examine the process of fulfilling a home ownership certificate to a home buyer based on an agreement to buy and sell housing associated with defaults made in the agreement and to determine the developer's responsibility towards the home buyer in fulfilling the home ownership certificate to the home buyer based on agreement to buy and sell housing.In this research, a sociological approach is used to see the correlation between the agreements made by the developer and the home buyer through the sale and purchase agreement (PPJB) in terms of fulfilling their responsibilities and responsibilities. Research is descriptive, using primary, secondary and tertiary legal materials with data collection techniques in the form of interviews and literature studies and analyzed qualitatively. In drawing conclusions researchers use deductive thinking methods.The sale and purchase agreement of houses in Prima Indah housing between the developers of PT Deputirindo Prima Mandiri and the home buyers did not run in accordance with the binding purchase agreement (PPJB) agreed by the parties. The developer cannot submit the house certificate as physical proof of the transfer of ownership of the house to several buyers even though the buyer has paid off his obligations. And in the implementation of the fulfillment of this certificate can not be done because of financial problems between the developer and the previous land owner. This study also saw that the developer (developer) could not carry out its responsibilities to fulfill obligations in the process of buying and selling carried out based on a binding purchase agreement (PPJB) agreed by the partiesKeywords: Agreement, Responsibility, Developer (Developer), Housing, Binding Agreement of Purchase (PPJB)